Efektivitas Kompres Aloe Vera terhadap Penurunan Suhu Tubuh Anak Demam Fisiologis: Studi di Polindes Bantur - Lulus Septiane Putri; Raden Maria Veronika Widiatrilupi (Yayasan Mandar Indonesia, 2026)
The World Health Organization (WHO) estimates that the number of fever cases in children reaches 62%. Management of fever can be in the form of non-pharmacological therapy. One of the non-pharmacological therapies for fever is the provision of compresses using aloe vera. Aloe vera contains lignin and saponins which can vasodilate the skin and lower body temperature. To determine the effect of aloe vera compresses on changes in body temperature in fever sufferers aged 4 – 6 years in the work area of the Bantur Health Center, Malang District. This study used one group pretest posttest with subjects of 16 children aged 4 – 6 years who had fever and lived in the work area of the Bantur Health Center. The sample in this study used a non-probability sampling technique with a purposive sampling method. The intervention carried out was the provision of aloe vera compresses on the forehead for 15 minutes. Temperature measurement using a digital thermometer. The data analysis used was univariate and bivariate analysis. The results of statistical tests using the Wilcoxon test stated that the administration of aloe vera compresses had an effect on changes in body temperature in fever sufferers with a p value = 0.001 (α <0.05) with a decrease in temperature of 0.5 ºC. Conclusion: There was a significant effect on the body temperature of fever sufferers before and after the administration of aloe vera compresses in the Bantur Polindes Work Area, Malang Regency.